Pelaksanaan Tukar Guling Tanah Kas Desa untuk Proyek Pembangunan Kajian pada Proyek Jalur Lingkar Timur Sukoharjo, Jawa Tengah - Suharto, Didik Gunawan; Aisyah Nur’ayni (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2021)
This research aims to analyze the process of implementing land swap policy for the village-owned site as the effect of East Ring Road Construction project in Sukoharjo Regency, Central Java, referring to Charles O. Jones’ implementation concept, and to identify inhibiting and supporting factors viewed from Van Meter and Van Horn’s implementation dimensions. Data collection was conducted through documentation and interviewing the representatives of Public Work Service Office, National Land Affairs Agency, and Village Community Empowerment Service Office of Sukoharjo Regency Government and Manisharjo Village Government. The result of research showed that the implementation of village land swap policy has been conducted referring to the existing regulation and fulfilled the components of organizational procedure, as suggested by Jones. In application stage, up to this research period the swap activity has been implemented from planning, preparation, to implementation process. Meanwhile, the process of transferring output has not been done yet. Some factors supporting this policy implementation: the existence of activity standard and target, the competent human resource, the good cross-sector relationship, and the compatibility of implementing agent characteristics to the assignment given. Meanwhile, the inhibiting factors were found related to limited fund source, implementer disposition, and political situation in Sukoharjo Regency around Local Leader Election (Pilkada) and Covid-19 pandemic incidence.